Association of Healthy Eating Index and the Alternative Healthy Eating Index with the cell blood count indices - Saberi-Karimian, Maryam; Ghazizadeh, Hamideh; Kabirian, Marzieh; Barati, Elham; Sheikh Andalibi, Mohammad Sobhan; Khakpour, Smaneh; Safari, Mina; Baghshani, Mohammad Reza; Parizadeh, Seyed Mostafa; Tayefi, Maryam; Ferns, Gordon A.; Ghayour-Mobarhan, Majid (Acta Biomedica Atenei Parmensis, 2021)
Objectives: There is an association between diet quality and markers of inflammation. We aimed to investigate the relationship between diet quality with cell blood count (CBC) and inflammatory indices such as red cell distribution width (RDW) and white blood cell count (WBC). Study Design: A total of 367 male subjects aged 20-69 yrs, who were employees of Shahid Hasheminejad Gas Processing Company (SGPC) completed the study. Methods: All participants completed a questionnaire that contained questions about demography. Standard protocols were used for measuring anthropometric indices in all subjects. Blood samples were collected after a 12 hrs fast from all participants. Biochemical parameters were determined in all participants using an auto-analyzer (Eppendorf, Germany). Systolic and diastolic blood pressure were measured using a standard mercury sphygmomanometer. CBC was measured using the Sysmex auto analyser system (KX-21 N). The HEI/AHEI scores extracted from a validated food frequency questionnaire (FFQ) to evaluate the diet quality. Data analyses were performed using SPSS 16 (SPSS Inc., IL, and USA). Results: A total of 674 men (aged 43.68±9.09 yrs) completed the study. The CBC indices were not significantly different between the HEI/AHEI classifications among the Iranian men (p-value >0.05 for all variables). Moreover, there was no association between HEI/ AHEI with the CBC indices in our population (p-value >0.05 for all variables). Conclusions: In summary, there was no association between the diet quality with the cell blood count parameters among Iranian men.